Analysis of Availability Efficiency, Performance Efficiency, And Quality Efficiency Using the Overall Equipment Effectiveness (OEE) Method: Case Study in the Service Unit of Orya Hydro Power Plant of Jayapura Regency - Hutapea, Vico Metriwan Perluozon; Sutjipto, Mohammad Riza; Witjara, Edi; Pasaribu, Rina Djunita (West Science Business and Management, 2024)
This study investigates the Orya Jayapura Hydroelectric Power Plant in Indonesia. The plant suffers from high machine downtime, resulting in low production and profits. Analyze the plant's efficiency using the Overall Equipment Effectiveness (OEE) method. OEE considers availability, performance, and quality metrics. A mixed method combining a case study with quantitative data analysis (OEE formula) and a qualitative approach (cause-and-effect diagrams) to prioritize improvement recommendations. The average OEE for 2019-2022 was only 32.76%, indicating significant equipment inefficiency and low profits. High equipment failure losses were identified as the main culprit. The study confirms a correlation between technical efficiency and financial performance: higher availability leads to higher profits. The plant needs to improve its overall quality in terms of people, machinery, materials, and methods. This includes staffing with qualified personnel, providing employee training, enhancing equipment maintenance, and implementing strategies for asset optimization and innovation.